A high-strength and low-loss soft magnetic alloy composite material and preparation method thereof

Fine-grained soft magnetic alloy powders are prepared through rapid cooling and surface modification technology, and glass coating and pressure sintering processes are adopted to solve the problem of large eddy current loss of soft magnetic alloy materials at high frequencies, and a soft magnetic alloy composite material with high strength, low loss and high reliability is achieved.

CN116646139BActive Publication Date: 2025-04-22CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310624503.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-30
Publication Date
2025-04-22
Estimated Expiration
2043-05-30

AI Technical Summary

Technical Problem

The existing soft magnetic alloy materials have large eddy current losses at high frequency, resulting in serious heat generation. The conventional resin impregnation process increases the strength of magnets by a small amplitude and aging problems, resulting in poor reliability.

Method used

The fine-grained soft magnetic alloy powder is prepared by rapid cooling, and surface modification and glass coating technology are used, combined with pressure sintering technology, to improve the resistivity and binding force between particles, reduce eddy current losses and increase magnet strength.

Benefits of technology

A soft magnetic alloy composite material with high strength and low loss is realized, which meets the needs of high frequency, low power consumption and high reliability, improves the resistivity of the material and the bonding force between particles, and reduces eddy current loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116646139B_ABST
    Figure CN116646139B_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and low-loss composite material and a preparation method thereof. Soft magnetic alloy material is smelted to obtain alloy liquid, the alloy liquid is sprayed out from a spray plate and then cooled in a nitrogen atmosphere to obtain soft magnetic alloy powder, a coupling agent is used to perform surface modification on the soft magnetic alloy powder to obtain modified powder, the modified powder is mixed with glass powder to obtain mixed powder, the mixed powder is mixed with resin and granulated to obtain pellets, the pellets are pressed and molded to obtain a magnetic ring, and the magnetic ring is sintered to obtain a soft magnetic alloy composite material. In the invention, scientific component design and reasonable matching process design of the alloy powder are important for reducing the power consumption of the material and improving the strength of the magnetic element. The high-reliability and low-loss soft magnetic alloy material newly developed and prepared by the method substantially solves the difficult problem of soft magnetic alloy material application under high frequency and high current conditions in automotive electronics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft magnetic alloy material preparation, and in particular to a high-strength and low-loss composite material and a preparation method thereof. Background Art

[0002] With the popularization of automotive electronics and the increasing demand for automotive functions, the power of DC-DC power supplies is getting higher and higher. This type of DC-DC power supply has the characteristics of high frequency, low voltage and high current. Although ordinary soft magnetic materials are suitable for high frequencies, they are difficult to meet the requirements of high current due to their low Bs and easy saturation. Soft magnetic alloy materials are increasingly used in such high-power scenarios due to their high Bs, high magnetic permeability, excellent current superposition and high Curie temperature. However, conventional soft magnetic alloy materials have low resistivity and large eddy current loss at high frequencies, resulting in severe heat loss and high loss, which limits their use at high frequencies. In the face of the requirements of electronic devices for high frequency, low power consumption and high reliability, on the one hand, it is necessary to improve the resistivity of soft magnetic alloy materials to reduce the high-frequency loss of materials. It is difficult to increase the resistivity by conventional coating, and innovative insulation coating is required on the surface of alloy powder. On the other hand, in order to improve the strength of components and thus improve their reliability in automobiles, the current soft magnetic alloys generally use the process of impregnating resin after sintering to improve the strength of the magnet. However, the process of impregnating resin has a small improvement in the strength of the magnet and the resin has the problem of aging, resulting in poor reliability. The existing low-loss material particles have poor bonding strength, and there is an aging risk by increasing the strength through resin impregnation. Summary of the invention

[0003] In order to solve the problems of the prior art, the first purpose of the present invention is to provide a method for preparing a high-strength and low-loss soft magnetic alloy composite material. The preparation method of the present invention is to ensure that the grains inside the metal particles are small by rapid cooling to reduce the eddy current loss of the material, to make the glass better dispersed and adsorbed on the surface of the metal powder by surface modification, and to make the glass evenly distributed between the particles by sintering through a pressure sintering process, thereby increasing the resistivity between the particles and reducing the eddy current loss and increasing the bonding force between the particles. By using this method, a high-strength and low-loss soft magnetic alloy material can be prepared.

[0004] The second object of the present invention is to provide a high-strength and low-loss soft magnetic alloy composite material obtained by the above-mentioned preparation method. The soft magnetic alloy composite material provided by the present invention has small grains inside the particles and dense and uniform glass microlayers between the particles, which can meet the current device requirements for high frequency, low loss, high strength and high reliability.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] The invention discloses a method for preparing a high-strength and low-loss soft magnetic alloy composite material, comprising the steps of melting a soft magnetic alloy material to obtain an alloy liquid, spraying the alloy liquid from a spray plate and cooling it in a nitrogen atmosphere to obtain a soft magnetic alloy powder, using a coupling agent to perform surface modification on the soft magnetic alloy powder to obtain a modified powder, mixing the modified powder with a glass powder to obtain a mixed powder, mixing the mixed powder with a resin and granulating the mixture to obtain a pellet, pressing the pellet to obtain a magnetic ring, and sintering the magnetic ring to obtain the soft magnetic alloy composite material;

[0007] The soft magnetic alloy material has the following components, calculated by mass percentage: Fe 90.75wt%-94.97wt%, Si 2.9wt%-4.5wt%, Al 2.0wt%-4.0wt%, B 0.1wt%-0.5wt%, Mn 0.01wt%-0.05wt%, Ca 0.01wt%-0.15wt%, Ni 0.01wt%-0.05wt%.

[0008] The soft magnetic alloy material of the present invention can make the magnetic anisotropy constant and hysteresis expansion coefficient of the material approach zero by controlling Fe / Si / Al within the scope of the present invention, thereby reducing magnetic loss. At the same time, the addition of elements such as B and Mn can inhibit the growth of grain size and reduce internal eddy current loss.

[0009] Further preferably, the soft magnetic alloy material has the following composition by mass percentage:

[0010] Fe90.75wt%~94.88wt%, Si2.9wt%~4.5wt%, Al2.0wt%~4.0wt%, B0.1wt%~0.5wt%, Mn0.01wt%~0.05wt%, Ca0.01wt%~0.15wt%, Ni0.01wt%~0.05wt%.

[0011] Preferably, the smelting temperature is 1300-1500°C.

[0012] In a preferred solution, the nitrogen atmosphere has a pressure of ≥5 MPa. In the present invention, a relatively large nitrogen pressure is used to increase the cooling rate, which, combined with the alloy composition of the present invention, can achieve the effect of grain refinement.

[0013] In a preferred embodiment, the particle size of the soft magnetic alloy powder is 3 to 25 μm. The inventors have found that the performance of the final soft magnetic alloy composite material is optimal when the particle size of the soft magnetic alloy powder is controlled within the above range. If the particle size is too small, the magnetic permeability is low, and if the particle size is too large, the loss is too high.

[0014] In the actual operation process, a coupling agent is added to the obtained soft magnetic alloy powder for surface modification, wherein the solvent is preferably a non-polar low boiling point solvent such as acetone or butanone.

[0015] In a preferred embodiment, the coupling agent is selected from silane coupling agents.

[0016] In actual operation, the soft magnetic alloy powder coupling agent is mixed with the soft magnetic alloy powder in a solvent, and the coupling agent is grafted onto the surface of the soft magnetic alloy powder to obtain the modified powder.

[0017] In a preferred embodiment, the coupling agent is added in an amount of 0.01% to 0.1% of the mass of the soft magnetic alloy powder.

[0018] In a preferred embodiment, the glass powder has a particle size of 0.1 μm to 0.5 μm.

[0019] In a preferred embodiment, the glass powder is selected from SiO 2 -B 2 O 3 -Al 2 O 3 - Glass-like, preferably SiO 2 -B 2 O 3 -Al 2 O 3 -ZnO glass, wherein the glass powder contains SiO 2 Content ≤65wt%, B 2 O 3 Content ≤15wt%.

[0020] The inventors found that the use of SiO 2 -B 2 O 3 -Al 2 O 3 -like glass has good wettability with the soft magnetic alloy powder in the present invention and good interface bonding. In the actual exploration process, the inventors tried a large number of glass powders, such as SiO 2 -CaO-Na 2 OP 2 O 5 -F glass has insufficient surface wettability with the soft magnetic alloy powder of the present invention, poor interface bonding strength, and poor strength improvement effect.

[0021] In a preferred embodiment, the resin is a mixed resin consisting of PVB resin and silicone resin, wherein the mass ratio of the resin is PVB resin: silicone resin = 1-3:7-9.

[0022] The inventors found that by controlling the properties of PVB resin and silicone resin within the above range, the performance of the final soft magnetic alloy composite material is optimal. If PVB resin is used, the insulation of the soft magnetic alloy composite material will deteriorate, and too little will affect the molding effect.

[0023] In a preferred embodiment, the resin is added in an amount of 1.0 wt% to 3.0 wt% of the mixed powder.

[0024] Preferably, the pressure of the compression molding is 1500-2500 MPa.

[0025] In a preferred embodiment, the sintering process is to first sinter at normal pressure in an air atmosphere and then sinter under pressure in a protective atmosphere; the process of the normal pressure sintering is to first keep the temperature at 120°C to 150°C for 1 to 3 hours and then keep the temperature at 320°C to 360°C for 1 to 4 hours; during the pressure sintering, the gas pressure in the furnace is maintained at 20MPa to 100MPa before 700°C, then the temperature is raised to 700°C to 750°C and kept for 0.5h to 1h, and the pressure during the keeping temperature is controlled to be 10 to 30MPa.

[0026] The sintering process of the present invention first adopts normal pressure sintering to allow the volatile substances of PVB and silicone resin to be separated from the magnet after decomposition, and then adopts pressure sintering under a protective atmosphere. Because the glass begins to crystallize in the pressure sintering temperature range, the exchange penetration between the glass part and the particle surface is promoted by pressure, so that the particles and the glass layer are tightly combined, thereby improving the strength of the magnet.

[0027] Further preferably, the protective atmosphere is a nitrogen atmosphere.

[0028] The inventors found that the present invention needs to be sintered in a protective atmosphere. If it is sintered in air, the magnetic permeability will be too low.

[0029] The present invention also provides a high-strength and low-loss soft magnetic alloy composite material prepared by the above preparation method.

[0030] Principles and advantages

[0031] The present invention firstly reduces the internal eddy current of the soft magnetic alloy powder by optimizing and matching the material composition, and secondly, makes the glass densely and evenly filled and bonded between the soft magnetic alloy powders by the combined action of glass coating and matching sintering process, greatly improves the resistivity between the soft magnetic alloy particles, reduces the high-frequency eddy current loss, and improves the bonding strength between the particles. The above scheme can not only reduce the loss, but also ensure the strength and anti-aging of the device and improve the reliability, which can fundamentally solve the application problem of soft magnetic alloy in automotive electronics.

[0032] Generally speaking, the scientific composition design and reasonable matching process design of the alloy powder in the present invention play an important role in reducing the power consumption of the material and improving the strength of the magnetic component. The high-reliability, low-loss soft magnetic alloy material newly developed and prepared by this method substantially solves the difficult problem of applying soft magnetic alloy materials under high frequency and high current conditions in automotive electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 : SEM image of the powder of Example 1. It can be seen from the figure that the surface of the particles is covered with a uniform layer of glass powder.

[0034] Figure 2 : SEM image of powder in Comparative Example 6. It can be seen from the figure that there is no coated powder on the surface of the particles. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below. The described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0036] Embodiment 1:

[0037] An alloy material is selected, and its material composition is 90.75wt% Fe, 4.5wt% Si, 4.0wt% Al, 0.5wt% B, 0.05wt% Mn, 0.15wt% Ca, and 0.05wt% Ni. The alloy material is placed in a smelting furnace at 1500°C for smelting, and then sprayed out into alloy powder through a spray plate, and cooled in a nitrogen atmosphere, wherein the nitrogen pressure is 6MPa, and the alloy powder is cooled in nitrogen for 1.8 seconds. The particle size distribution of the prepared alloy material powder is in the range of 3μm to 25μm. After the surface of the alloy powder is cleaned with a solvent, 0.01wt% of a coupling agent is added to modify the surface of the material; the solvent is acetone, and the coupling agent is preferably triethoxysiloxane. After completion, the powder is dried, and 1.0wt% of glass powder is added to form a mixed powder, wherein the glass powder particle size is 0.1μm, and the glass powder component is preferably SiO 2 -B 2 O 3 -Al 2 O 3 -ZnO glass, in which SiO 2 Content 70wt%, B 2 O 3 The content is 12wt%. The mixed powder is added to PVB and silicone resin to form granulated powder, and pressed under a pressure of 1500MPa to form a magnetic ring; the magnetic ring is placed in a nitrogen furnace and sintered in a nitrogen atmosphere to form a final product. In the mixed resin of PVB and silicone resin, the mass ratio of PVB: silicone resin is 1:9, and the mass ratio of the mixed resin to the mixed powder is 1.0wt%. Before sintering, air is preferably introduced before 320°C, kept at 120°C for 1 hour, kept at 320°C for 4 hours, and then the magnetic ring is placed in a nitrogen furnace again, and the air pressure in the furnace is maintained at 100MPa before 700°C, the maximum sintering temperature is 700°C, and kept warm for 1 hour. The sintering pressure is maintained at 30MPa.

[0038] Embodiment 2:

[0039] An alloy material will be selected, and its material composition is 94.88wt% Fe, 2.9wt% Si, 2.0wt% Al, 0.1wt% B, 0.01wt% Mn, 0.01wt% Ca, and 0.01wt% Ni. The alloy material is placed in a smelting furnace at 1300°C for smelting, and then sprayed out into alloy powder through a spray plate, and cooled in a nitrogen atmosphere, wherein the nitrogen pressure is 8MPa, and the alloy powder is cooled in nitrogen for 1.5 seconds. The particle size distribution of the prepared alloy material powder is in the range of 3μm to 25μm. After the surface of the alloy powder is cleaned with a solvent, 0.1wt% of a coupling agent is added to modify the surface of the material; wherein the solvent is preferably butanone, and wherein the coupling agent is preferably trimethoxysilane. After completion, the powder is dried, and 0.1wt% of glass powder is added to form a mixed powder, wherein the glass powder particle size is preferably 0.5μm, and wherein the glass powder component is preferably SiO 2 -B 2 O 3 -Al 2 O 3 -ZnO glass, in which SiO 2 Content 65wt%, B 2 O 3 The content is 10wt%. The mixed powder is added to PVB and silicone resin to form a granulated powder, and pressed under a pressure of 2500MPa to form a magnetic ring; the magnetic ring is placed in a nitrogen furnace and sintered in a nitrogen atmosphere to form a final product. In the mixed resin of PVB and silicone resin, the mass ratio of PVB: silicone resin is 3:7, and the mass ratio of the mixed resin to the mixed powder is 3.0wt%. Before sintering, air is preferably introduced before 360°C, and the temperature is kept at 150°C for 1 hour, and the temperature is kept at 360°C for 1 hour. Then, the magnetic ring is placed in a nitrogen furnace again, and the pressure in the furnace is kept at 20MPa before 700°C, the maximum sintering temperature is 750°C, the temperature is kept constant for 0.5h, and the pressure is kept at 10MPa.

[0040] Embodiment 3:

[0041] An alloy material is selected, and its material composition is 93.35wt% Fe, 3.5wt% Si, 2.8wt% Al, 0.2wt% B, 0.02wt% Mn, 0.10wt% Ca, and 0.03wt% Ni. The alloy material is placed in a smelting furnace at 1400°C for smelting, and then sprayed out into alloy powder through a spray plate, and cooled in a nitrogen atmosphere, wherein the nitrogen pressure is 6MPa, and the alloy powder is cooled in nitrogen for 1 second. The particle size distribution of the prepared alloy material powder is in the range of 3μm to 25μm. After the surface of the alloy powder is cleaned with a solvent, 0.05wt% to 100wt% of a coupling agent is added to modify the surface of the material; wherein the solvent is preferably acetone, and wherein the coupling agent is preferably a silane coupling agent trimethoxysilane. After completion, the powder is dried, and 0.05wt% of glass powder is added to form a mixed powder, wherein the glass powder particle size is preferably 0.2μm, and wherein the glass powder component is preferably SiO 2 -B 2 O 3 -Al 2 O 3 -ZnO glass, in which SiO 2 Content 70wt%, B 2 O 3 The content is 9wt%. The mixed powder is added to PVB and silicone resin to form granulated powder, and pressed under a pressure of 2000MPa to form a magnetic ring; the magnetic ring is placed in a nitrogen furnace and sintered in a nitrogen atmosphere to form a final product. In the mixed resin of PVB and silicone resin, the mass ratio of PVB: silicone resin is 2:8, and the mass ratio of the mixed resin to the mixed powder is 2.0wt%. Before sintering, air is preferably introduced before 340°C, and the temperature is kept at 130°C for 1 hour and at 350°C for 2 hours. The magnetic ring is then placed in a nitrogen furnace, and the pressure in the furnace is maintained at 50MPa before 700°C. The maximum sintering temperature is 730°C, the temperature is kept constant for 0.8H, and the pressure is maintained at 20MPa.

[0042] Comparative Example 1:

[0043] Other conditions were the same as those in Example 1, except that the melting temperature was 1250° C. Since the molten steel was viscous and the particle size was too large, the material with the desired particle size could not be obtained.

[0044] Comparative Example 2:

[0045] The other conditions were the same as those in Example 1, except that the nitrogen pressure was 3 MPa.

[0046] Comparative Example 3:

[0047] The other conditions are the same as those in Example 1, except that the particle size distribution of the prepared alloy material powder is in the range of 26 μm to 75 μm.

[0048] Comparative Example 4:

[0049] The other conditions are the same as those in Example 1, except that the Al composition of the material is adjusted to 6.0wt%, and the specific composition is 88.75wt% Fe, 4.5wt% Si, 6.0wt% Al, 0.5wt% B, 0.05wt% Mn, 0.15wt% Ca, and 0.05wt% Ni.

[0050] Comparative Example 5:

[0051] The other conditions are the same as those in Example 1, except that elements such as Mn and Ca are removed from the material. The specific composition is 91wt% Fe, 4.5wt% Si, 4.0wt% Al, and 0.5wt% B.

[0052] Comparative Example 6:

[0053] The other conditions were the same as those in Example 1, except that the glass coating layer was removed.

[0054] The performance of the sintered magnetic rings of the embodiment and the comparative example was evaluated. The number of winding turns N=13Ts turns. The magnetic permeability μ (1V / 1MHz) of the magnetic ring samples was tested using a 3260B LCR tester and the collapse strength of the magnetic ring was tested using an electronic universal testing machine SH-100. The power consumption of the magnetic ring was tested using an IWATSU-SY-8218 hysteresis loop instrument, 50mT&1MHz). The obtained performance data are shown in Tables 1 and 2 respectively:

[0055] Table 1 Performance data of the embodiment

[0056]

[0057]

[0058] Table 2 Performance data of comparative examples

[0059]

[0060] Through the performance comparison of the embodiments and the comparative examples in Table 1 and Table 2, it can be seen that the composition and process of the embodiments are within the scope of the patent, the power consumption of the obtained material is significantly lower than that of the comparative example, and the strength is significantly improved, which shows that the present invention is feasible and has great performance advantages.

[0061] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the patent protection scope of the present invention determined by the submitted claims.

Claims

1. A method for preparing a high-strength and low-loss soft magnetic alloy composite material, characterized in that: The soft magnetic alloy material is melted to obtain alloy liquid, and after the alloy liquid is sprayed out from the spray plate, it is cooled in a nitrogen atmosphere to obtain soft magnetic alloy powder, the soft magnetic alloy powder is surface-modified by a coupling agent to obtain modified powder, the modified powder is mixed with glass powder to obtain mixed powder, the mixed powder is mixed with resin and granulated to obtain pellets, the pellets are pressed and molded to obtain magnetic rings, and the magnetic rings are sintered to obtain soft magnetic alloy composite materials; The gas pressure of the nitrogen atmosphere is ≥5MPa; The glass powder is selected from SiO2-B2O3-Al2O3-type glass, wherein the content of SiO2 in the glass powder is ≤65wt%, and the content of B2O3 is ≤15wt%; The resin is a mixed resin composed of PVB resin and silicone resin, wherein the mass ratio of the resin is PVB resin: silicone resin = 1-3:7-9; The sintering process is to first sinter at normal pressure in an air atmosphere and then sinter at pressure in a protective atmosphere; The process of the atmospheric pressure sintering is: first, keep the temperature at 120°C-150°C for 1-3 hours, then keep the temperature at 320°C-360°C for 1-4 hours, and during the pressure sintering, keep the gas pressure in the furnace at 20MPa-100MPa before 700°C, then increase the temperature to 700°C-750°C, keep the temperature for 0.5h-1h, and control the pressure during the insulation process to be 10-30MPa; The soft magnetic alloy material has the following components, calculated by mass percentage: Fe 90.75wt%~94.97wt%, Si2.9wt%~4.5wt%, Al 2.0wt%~4.0wt%, B 0.1wt%~0.5wt%, Mn0.01wt%~0.05wt%, Ca 0.01wt%~0.15wt%, and Ni 0.01wt%~0.05wt%.

2. The method for preparing a high-strength and low-loss soft magnetic alloy composite material according to claim 1, characterized in that: The smelting temperature is 1300-1500°C.

3. The method for preparing a high-strength and low-loss soft magnetic alloy composite material according to claim 1, characterized in that: The particle size of the soft magnetic alloy powder is 3-25 μm.

4. The method for preparing a high-strength and low-loss soft magnetic alloy composite material according to claim 1, characterized in that: The coupling agent is selected from silane coupling agents; The added amount of the coupling agent is 0.01% to 0.1% of the mass of the soft magnetic alloy powder.

5. The method for preparing a high-strength and low-loss soft magnetic alloy composite material according to claim 1, characterized in that: The particle size of the glass powder is 0.1µm-0.5µm.

6. The method for preparing a high-strength and low-loss soft magnetic alloy composite material according to claim 1, characterized in that: The added amount of the resin is 1.0wt% to 3.0wt% of the mixed powder mass.

7. The method for preparing a high-strength and low-loss soft magnetic alloy composite material according to claim 1, characterized in that: The pressure of the pressing molding is 1500~2500MPa.

8. A high-strength and low-loss soft magnetic alloy composite material prepared by the preparation method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • High-permeability and high-saturation magnetically soft alloy material and preparation method thereof

    CN113096948A

  • High-strength low-loss composite soft magnetic material, method of manufacturing the same, and electromagnetic circuit part

    JP2011216571A